177k views
2 votes
What expression is equivalent to -3+2/3y-4-1/3y

User Pmarflee
by
5.7k points

1 Answer

3 votes

Answer:

The simplified form of the given expression is
-7 + ((1)/(3))y

Explanation:

Here, the given expression is:


-3 + ((2)/(3)) y - 4 - ((1)/(3))y

Now to simplify the given expression, perform operations on LIKE TERMS:

We get:


-3 + ((2)/(3)) y - 4 - ((1)/(3))y  =( -3  - 4)  + [((2)/(3)) y- ((1)/(3))y]\\= - 7  + [((2)/(3)) -((1)/(3))]y  = -7 + [(2-1)/(3)]y\\ = -7 + ((1)/(3))y\\ \implies -3 + ((2)/(3)) y - 4 - ((1)/(3))y =   -7 + ((1)/(3))y

Hence the simplified form of the given expression is
-7 + ((1)/(3))y

User Bhavik Shah
by
6.2k points